Function of caspase-14 in trophoblast differentiation - White, L.; Declercq, W.; Arfuso, Frank; Charles, A.; Dharmarajan, Arunasalam (2009)
Background: Within the human placenta, the cytotrophoblast consists of a proliferative pool of progenitor cells which differentiate to replenish the overlying continuous, multi-nucleated syncytiotrophoblast, which forms the barrier between the maternal and fetal tissues. Disruption to trophoblast differentiation and function may result in impaired fetal development and preeclampsia. Caspase-14 expression is limited to barrier forming tissues. It promotes keratinocyte differentiation by cleaving profilaggrin to stabilise keratin intermediate filaments, and indirectly providing hydration and UV protection. However its role in the trophoblast remains unexplored. Methods: Using RNA Interference the reaction of control and differentiating trophoblastic BeWo cells to suppressed caspase-14 was examined for genes pertaining to hormonal, cell cycle and cytoskeletal pathways. Results: Transcription of hCG, KLF4 and cytokeratin-18 were increased following caspase-14 suppression suggesting a role for caspase-14 in inhibiting their pathways. Furthermore, hCG, KLF4 and cytokeratin-18 protein levels were disrupted. Conclusion: Since expression of these molecules is normally increased with trophoblast differentiation, our results imply that caspase-14 inhibits trophoblast differentiation. This is the first functional study of this unusual member of the caspase family in the trophoblast, where it has a different function than in the epidermis. This knowledge of the molecular underpinnings of trophoblast differentiation may instruct future therapies of trophoblast disease. © 2009 White et al; licensee BioMed Central Ltd.